Faktor Positif Kebudayaan Barat Dalam Meningkatkan Pendidikan Agama Islam - Pebriadi Surya Pemungkas; Nur Annisa Ummardiyyah; Muhammad Firman Ardinata; Canifudin Canifudin (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This study examines the positive factors of Western culture that contribute to enhancing Islamic religious education. Western culture brings forth various influences that can positively impact the development of Islamic religious education. The study explores factors such as increased access to information, innovative educational approaches, critical thinking, and the promotion of pluralism and tolerance. These factors provide opportunities for Muslims to broaden their knowledge and deepen their understanding of Islamic teachings through wider access to information, engaging educational methods, and the development of critical thinking skills. Additionally, Western culture's emphasis on pluralism and tolerance can contribute to fostering a more inclusive and harmonious environment within Islamic religious education. By analyzing and utilizing these positive factors, Islamic religious education can be enriched and made more relevant in the context of contemporary challenges while upholding the core values of Islam.